Synthesis of ZnO Nanostructures for Photoluminescent Ink Applications - Thanh Phuong Nguyen,; Ngoc Nhung Thi Nguyen,; Phuong Trinh Le Nguyen, (Journal of Technical Education Science, 2025)
In this study, we have successfully synthesized ZnO nanoparticles (ZnO NPs) using co-precipitation and hydrothermal methods. ZnO NPs were fabricated by co-precipitation for spherical shape, while the hydrothermal method was for rod-shaped morphology. The XRD analysis shows that ZnO NPs possess a hexagonal wurtzite structure for two synthesis methods. The UV-Vis spectra analysis shows that the ZnO NPs have an absorption peak at the wavelength of 355 nm. The PL spectra result reveals that ZnO NPs synthesized by co-precipitation have two peaks at about 570 nm and 650 nm, while ZnO nano-rods synthesized by the hydrothermal method have a PL peak at 650 nm. Luminescent inks based on ZnO nano-rods and nano spherical particles were printed on filter paper using a screen printing method. The logos of the“Faculty of Graphic Arts and Media” samples show bright yellow and pink fluorescence under UV irradiation 365 nm and are invisible under normal light.